Seasonal effects on the levels of some minerals of Iraqi one- humped females camels (Camelus dromedarius): Ahmed A. Amnate*, Anas Obaid Humadi**, Mohammed Jobair Muhaidi** Yassen Taha Abdul-Rahaman** - مناتي, أحمد عبد الرضا; عبيد حمادي, أناس; مهيدي, محمد جبير; عبد الرحمن, ياسين طه (Journal of Kerbala for Agricultural Sciences, 2016)
Twelve Iraqi one-humped female camels (Camelus dromedarius) of 7- 8 years old presented in the Animal Farm, College of Veterinary Medicine, University of Anbar were used in this study during the period of 1/9/2012 to 1/1/2013. The study were designed to find out the effect of season of year on the levels of some minerals. The results showed there is no significant effects of months on Calcium and Potassium. The results also showed that Phosphorous and Sodium were increased during September (P<0.05) and decreased in other months. Magnesium was increased significantly (P<0.05) during December (P<0.05) as compared with other months. In Conclusion, there are variation between the present findings and those from previous studies that may be attributed to the season or months. Keywords: Camel, minerals, months. تأثير الأشهر على مستويات بعض المعادن في إناث الابل وحيدة السنام العراقية أحمد عبد الرضا مناتي*، أناس عبيد حمادي**، محمد جبير مهيدي** ياسين طه عبد الرحمن** كلية الزراعة/ جامعة كربلاء* كلية الطب البيطري/ جامعة الفلوجة** المستخلص استخدمت في هذه الدراسة أثنا عشر أنثى من الجمال العراقية وحيدة السنام بعمر 7-8 سنة تواجدت في حقل كلية الطب البيطري، جامعة الأنبار، خلال الفترة من الأول من أيلول 2012 إلى الأول من كانون الثاني 2013. صممت هذه التجربة لمعرفة تأثير بعض أشهر السنة على مستويات بعض المعادن في دم الابل. أظهرت النتائج عدم وجود تأثير معنوي للأشهر على الكالسيوم والبوتاسيوم. كما أظهرت النتائج أن مستويات الفسفور والصوديوم كانت مرتفعة (P<0.05) خلال شهر أيلول وانخفضت خلال الأشهر المختلفة. كان المغنسيوم مرتفعاً (P<0.05) خلال كانون الأول مقارنة بالأشهر الأخرى. نستنتج من الدراسة أن هنالك تباين بين النتائج الحالية ونتائج الدراسات السابقة والذي يمكن أن يعزى إلى تأثير الموسم وأشهر التقييم. الكلمات المفتاحية: إبل، معادن، الأشهر.